Polymer based solutions of bupranolol hydrochloride for intranasal systemic delivery - Mishra B.; Sankar C.; Mishra M. (My University, 2025)
The present study was aimed at developing intranasal polymer based solutions as alternative route for systemic delivery of Bupranolol hydrochloride (BPH). It is a potent β-blocker drug which upon oral administration undergoes extremely high hepatic first-pass metabolism (>90% in humans). The polymeric solutions were prepared using varying concentrations of polymers like sodium alginate, chitosan, sodium carboxymethylcellulose, methylcellulose (MC), polyvinyl alcohol, carbopol, hydroxypropyl MC, and hydroxypropyl cellulose. The prepared formulations were evaluated in terms of pH of the solution, angular viscosity, drug content, gel strength, gelation temperature, in vitro drug release, in vivo pharmacodynamic studies, histopathological, and stability studies. Except MC based solutions, a biphasic pattern of drug release was obtained in all other cases. Nasal administration of selected batches of polymeric solutions were found to be nontoxic and were able to improve drug bioavailability when compared to oral, nasal, and intravenous solution administrations of BPH. © 2011 Informa UK, Ltd.